Managing public-private joint venture companies : the case of Zimbabwe's diamond mining sector - Mlilo, Bongiwe Ntombikayise (My University, 2016)
ABSTRACT The purpose of this study is to analyse the strategic management of public-private joint ventures in Zimbabwe’s diamond-mining in the context of a challenging economic environment and consistently changing policies. Joint ventures have been observed to face numerous issues unique to their business form. One of the challenges includes high levels of failure due to among others, cultural and strategic differences. With joint venture firms between Zimbabwe and China having increased in recent years, the study addresses the question of who the dominant partner is in terms of decision-making between the Zimbabwean and Chinese partners. The study also teases out issues such as what are the typologies of joint venture firms in the diamonds mining sector of Zimbabwe; what is the nature and condition of managerial business in the transnational private-public joint venture arrangements, and; how have policy pronouncements contributed to the shaping the business environment for firms involved in diamond-mining firms? To carry out the study, a qualitative research design was employed. This relied on data collected through semi-structured interviews, observations and informal interviews with managers at mining joint-venture firms as well as representatives of organisations responsible for monitoring and regulation within the mining industry. The study used a convenience sampling approach to identify management from three firms based in two sites were chosen in Zimbabwe namely Harare and Mutare. The study reveals that decision-making is a complex process involving the state through policy and Chinese parent companies. However, because of the dominance of policy, the state -through Zimbabwean partners in the joint ventures- dominates strategy and decision-making. The Chinese firms may devise their own strategy but ultimately it must be streamlined. The study also reveals that while policy plays a large role, it is complicated because of inconsistencies and lack of clarity in some areas. This is highlighted in the continuously changing indigenisation policy and apparent reference to ZIMASSET as the primary policy instead of the mining policy. The result is a type of joint venture which is consistent with Drucker’s dual nationality typology where separate but not necessarily conflicting interests dominate. The study contributes to the literature on mining operations in Zimbabwe which range from political economy to commercial fields. Evidence in this thesis is telling in terms of i the dynamics of decision-making in joint venture management in Zimbabwe especially involving transnational ties.
MBA Thesis
Keywords: Diamond industry and trade, Public-private sector cooperation, Joint ventures -- Zimbabwe.